1998
DOI: 10.1073/pnas.95.6.3122
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal trefoil factor controls the expression of the adenomatous polyposis coli–catenin and the E-cadherin–catenin complexes in human colon carcinoma cells

Abstract: Intestinal trefoil factor 3 (TFF3) is a member of the trefoil family of peptides, small molecules constitutively expressed in epithelial tissues, including the gastrointestinal tract. TFF3 has been shown to promote migration of intestinal epithelial cells in vitro and to enhance mucosal healing and epithelial restitution in vivo. In this study, we evaluated the effect of recombinant TFF3 (rTFF3) stimulation on the expression and cellular localization of the epithelial (E)-cadherin-catenin complex, a prime medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(92 citation statements)
references
References 55 publications
5
86
1
Order By: Relevance
“…Moreover we found that mucin-primed IEC cells are more sensitive to ITF stimulation, speculating that the up-regulation of ITF-binding molecules might be physiologically relevant. Several groups have proposed the existence of a receptor-like molecule that is able to mediate ITF action [1,2,18,[22][23][24][25][26]. Further isolation and characterization of ITF-BP will shed light on the molecular mechanism of ITF action and intestinal epithelial cell biology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover we found that mucin-primed IEC cells are more sensitive to ITF stimulation, speculating that the up-regulation of ITF-binding molecules might be physiologically relevant. Several groups have proposed the existence of a receptor-like molecule that is able to mediate ITF action [1,2,18,[22][23][24][25][26]. Further isolation and characterization of ITF-BP will shed light on the molecular mechanism of ITF action and intestinal epithelial cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that : (1) specific ITF-binding sites exist in the gastric epithelium, crypt cells of small intestine and colon [22][23][24] ; (2) ITF-binding protein (ITF-BP) is a 50 kDa glycosylated intestinal membrane protein [22] ; (3) stimulation by ITF for 24 h (at concentrations as low as 1 nM) leads to cell detachment and to a decreased intracellular adhesion in human carcinoma cells [25] ; (4) ITF (100 nM) leads to the inhibition of extracellular signal-related protein kinase and the mitogenactivated protein kinase pathways in IEC-6 cells through the activation of tyrosine or dual-specific phosphatase [2] ; (5) ITF (10 nM) modulates EGF effects on intestinal epithelial ion transport [26] ; and (6) ITF effect is mediated by signal transduction pathways linked to the protein tyrosine kinase\tyrosine phosphatase pathway [2,18,25]. These observations strongly suggest that a receptor-like membrane protein might mediate the action of ITF.…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed in estrogen-responsive but not in estrogen-nonresponsive breast cancer cell lines and may play a role in promoting cell migration by controlling the expression of APC and E-cadherin-catenin complexes. 20,21 As discussed previously, TFF1 is a fairly well established predictive biomarker for estrogen therapy responsiveness TFF1. mRNA levels are reportedly increased by estradiol but not by progesterone, dexamethasone, or dihydrotestosterone.…”
Section: Wwwnaturecom/tpjmentioning
confidence: 90%
“…We therefore postulate that specific signals from the tumor microenvironment, e.g., by stromal cells, the extracellular matrix, or cytokines, which were already shown to have strong influence on the malignant phenotype of breast cancer (28), also regulate intracellular ␤-catenin distribution and subsequently the behavior of colon tumor cells. For instance, trefoil factors are described to induce nuclear translocation of ␤-catenin in colon carcinoma cells (29). A possible direct influence of the extracellular matrix was demonstrated by showing that activation of integrin linked kinase leads to transcriptional repression of the E-cadherin gene and nuclear accumulation of ␤-catenin (30).…”
Section: Discussionmentioning
confidence: 99%